ABA Visualized: A Visual Guidebook for Parents and Teachers. (August 2021) - Santamaria, Luke
This professional resource review examines how van Diepen and van Diepen's ABA Visualized: A Visual Guidebook for Parents and Teachers (2019) serves as a useful resource for parents and practitioners in managing the behavior issues of children with disabilities, including those with emotional and behavioral disorders. Information about applied behavior analysis (ABA) and the presentation of ABA strategies are appraised.